An improved noninvasive resonance method for water content characterization of Cultural Heritage stone materials. (September 2018) - Piuzzi, Emanuele; Pittella, Erika; Pisa, Stefano; Cataldo, Andrea; De Benedetto, Egidio; Cannazza, Giuseppe
Highlights: A microwave-based system for monitoring water content in stones is presented. A patch resonator, connected to a VNA, is used as a probe. Water content of stones was related to the resonant frequency of the resonator. Measurements were performed on 4 types of stone, for 5 levels of water content. Abstract: In this work, a noninvasive microwave-based system for monitoring water content of Cultural Heritage stone materials is presented. In particular, by placing a planar resonator in contact with the stone sample, an experimental relationship between resonant frequency and water content is obtained. To verify the suitability of the system, experimental tests are carried out on several types of stones: gentile; leccese; carparo; red brick; and red brick fabricated at high temperatures. The first three types of stones are typically found in Cultural Heritage structures, and they are particularly affected by deterioration and decay phenomena. As for the red bricks, they are found in buildings from the XVII Century. Measurements are performed for five levels of water content of the stone samples, and the empirical relationship between each considered water content level and the corresponding resonance frequency of the patch resonator are derived. To enhance the contact between the planar resonator and the rough surface of the stone, the patch is covered with a thin layer of soft silicon conductor. The obtained results demonstrate the robustness of the presented solution.